Духовність як узмістовлення професійної діяльності соціального працівника - Рудакевич, Оксана Мирославівна; Рудакевич, Оксана Мирославовна; Rudakevych, Oksana M. (Східноєвропейський національний університет імені Лесі Українки, 2014)
Вивчаючи природу та форми прояву духовності, з’ясовано, що цей загальнокультурний феномен є однією з головних характеристик українського народу, її виховним ідеалом. Стверджується, що в сучасному суспільстві проблема формування системи духовних цінностей є пріоритетною, позаяк існує потреба в побудові гуманітарно спрямованої держави та соціуму. Тому соціальний працівник, який працює у сфері «людина-людина», повинен усвідомлювати важливість ціннісно-етичної сфери своєї діяльності, адже духовність є домінантою у формуванні його високого рівня професійної майстерності. The article examines the nature of the notion «spirituality» and forms of its manifestation in conditions of cardinal and overall changes in society. In the course of the study the author finds out that general cultural phenomenon of spirituality is one of the main characteristics of the Ukrainian nation, its educative ideal. The author affirms that in the modern Ukrainian society the problem of formation of the system of spiritual values is the priority one, as there exists vivid need in formation of humanitarian aimed country and society. In conditions of political, economic and social crisis a future social worker who works in the sphere of «Human–human» should understand the importance of value–ethical sphere of his activity, as spirituality is dominant in the formation of high level of professional mastery of a social work specialist.
Spirituality as Means of Giving Content to Professional Activity of a Social Worker
Keywords: духовність; професійна майстерність; спеціаліст соціальної роботи; культура; spirituality; professional mastery; social work specialist; culture